Gamifying Vocabulary Learning: Students’ Perceptions of Kahoot! in a Junior High School Context - Putri, Aulya; Dewi, Desi Surlitasari; Shalehoddin, Shalehoddin (Universitas Sarjanawiyata Tamansiswa, 2025)
This study explores students’ perceptions of Kahoot! as a tool for vocabulary learning in a junior high school context, focusing on how it fulfills their motivational needs and enhances its acceptance. A qualitative approach was employed, utilizing semi-structured interviews, observations, and closed questionnaires to collect data from 20 seventh-grade students who used Kahoot! for vocabulary learning. The data were analyzed using descriptive statistics for the Likert scale questionnaire and content analysis for qualitative responses. The findings reveal that Kahoot! creates an enjoyable, interactive, and engaging learning environment, fostering positive experiences. Its gamified features, including competitive elements, sustain students’ motivtion and encourage active participation. Furthermore, students reported improved vocabulary retention facilitated by Kahoot!’s repetitive and manageable design. The platform’s intuitive interface enhances ease of use, allowing students to focus on learning without technological challenges. This study highlights Kahoot!’s potential to enhance vocabulary learning through gamified, student-centered experiences.